Spatial and temporal analyses of women's wellbeing in the Democratic Republic of the Congo - Malokele Nanivazo; Kristi Mahrt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper sets out to investigate the wellbeing of women in the Democratic Republic of the Congo (DRC). It undertakes spatial and temporal comparisons of women's wellbeing using data from the Demographic and Health Survey and the Multiple Indicator Cluster Survey. Using the multidimensional first-order dominance approach, the results reveal mixed evidence of improvement and deterioration of women's welfare across the DRC over a three-year period (2007 - 10).
Keywords: J16; I32; O55; C81; 330; poverty comparison; women; Democratic Republic of the Congo; wellbeing